Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/cid/ciz1059
|View full text |Cite
|
Sign up to set email alerts
|

Improved Diagnostics Help to Identify Clinical Features and Biomarkers That Predict Mycoplasma pneumoniae Community-acquired Pneumonia in Children

Abstract: Background. There are no reliable signs or symptoms that differentiate Mycoplasma pneumoniae (Mp) infection in communityacquired pneumonia (CAP) from other etiologies. Additionally, current diagnostic tests do not reliably distinguish between Mp infection and carriage. We previously determined that the measurement of Mp-specific immunoglobulin M antibody-secreting cells (ASCs) by enzyme-linked immunospot assay allowed for differentiation between infection and carriage. Using this new diagnostic test, we aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 42 publications
7
46
2
Order By: Relevance
“…This difference may be due to the different subjects and different locations of the study. Moreover, in contrast to our findings, Patrick et al recently suggest that a high CRP/PCT ratio (>400 lg/ng) was helpless to predict MP-related CAP in children [8]. This difference may be attributed to the different age compositions of the study populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This difference may be due to the different subjects and different locations of the study. Moreover, in contrast to our findings, Patrick et al recently suggest that a high CRP/PCT ratio (>400 lg/ng) was helpless to predict MP-related CAP in children [8]. This difference may be attributed to the different age compositions of the study populations.…”
Section: Discussioncontrasting
confidence: 99%
“…The increase of PCT contributes to the severity of the systemic bacterial infection and the poor prognosis [7]. Also, higher PCT levels can help to identify MP-CAP and viral CAP [8,9]. However, there are some researches that contradict these beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…However, its role in the development of CAP is unclear. Mycoplasma pneumoniae is a frequent cause of community-acquired respiratory infections in children and adults [ 33 ], but we found the RELM-β level of the Mp − group was significantly higher than that of the Mp + group. Regardless of whether the patient is infected with Mp , the concentration of RELM-β will also increase significantly as the patient’s disease gets worse.…”
Section: Discussioncontrasting
confidence: 55%
“…It has been reported that MP can colonize the nasopharynx for a long time without any clinical manifestation. Meyer Sauteur et al 37 detected MP DNA in 48% of healthy children tested as controls during their study, and Nilsson et al 33 were able to detect MP DNA for 7 weeks after the clinical symptoms, even though the patients were correctly treated with MLs. Further research would be necessary to clarify the impact of carriers in the community on infection transmission.…”
Section: Discussionmentioning
confidence: 93%